High-hydrophobicity coating for fan blade and preparation method of high-hydrophobicity coating
By introducing enhanced composite filler and branched double-bond self-healing polyurethane into polyurethane coatings, the problem of insufficient hydrophobicity, corrosion resistance and wear resistance of fan blade coatings is solved, and the self-repairing ability of the material is realized, which significantly improves the The performance and service life of the coating.
Patent Information
- Application Number
- CN202510019767.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2045-01-07
AI Technical Summary
In the application of fan blades, existing polyurethane coatings have problems such as hydrophobicity, corrosion resistance, wear resistance and no self-repair ability.
By introducing reinforced composite filler and branched double bond self-healing polyurethane into polyurethane, the hydrophobicity, corrosion resistance and wear resistance of the material are improved, and the self-healing of the material is achieved by introducing 4,4'-dicarboxydiphenyldisulfide Repair ability.
It significantly improves the hydrophobicity, corrosion resistance and wear resistance of fan blade coatings, and gives the material self-healing ability and extends the service life.
Smart Images

Figure CN119410259A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of hydrophobic coatings, and specifically refers to a highly hydrophobic coating for fan blades and a preparation method thereof. Background Art
[0002] With the rapid development of economy and the improvement of people's living standards, the demand for electricity is increasing. At present, the main source of electricity is still thermal power generation, but fossil fuels such as coal and oil are non-renewable energy sources. With the decreasing mining and storage, the waste gas generated by combustion is more polluting to the environment. Wind energy, as a clean and renewable energy, has received more and more attention. At present, the utilization rate of onshore wind power and offshore wind power is low, and there is still great room for development. With the continuous consumption of fossil energy, wind power generation will become the trend of future power development. The service life of wind turbines is generally set to 20 years. Wind turbine blades are an important component of them. The cost of blades is high and difficult to replace and maintain. They are easily damaged by erosion such as hail, dust, salt spray, freezing, rain and snow, which limits the development of wind power generation. Polyurethane coatings are generated by the reaction of polyisocyanates and polyols. The cured paint film contains amide groups and ester groups. Hydrogen bonds can be formed between molecules, which have good adhesion and weather resistance and can provide effective protection for the substrate.
[0003] The existing technologies currently have the following main problems: the polyurethane coating has insufficient hydrophobicity, corrosion resistance, and wear resistance and has no self-repairing ability. Summary of the invention
[0004] In view of the above situation, in order to overcome the defects of the prior art, the present invention provides a highly hydrophobic coating for wind turbine blades and a preparation method thereof. In order to solve the problem of poor performance of polyurethane coatings, the present invention proposes to introduce a reinforced composite filler into polyurethane to improve the hydrophobicity, corrosion resistance and wear resistance of the material, and prepare a polyurethane with double bonds in the side chain to be well combined with the filler. At the same time, 4,4'-dicarboxy diphenyl disulfide is introduced into the polyurethane coating to achieve the technical effect of self-repair of the material after damage.
[0005] In order to achieve the above-mentioned purpose, the technical solution adopted by the present invention is as follows: The present invention proposes a highly hydrophobic coating for wind blades, and the highly hydrophobic coating for wind blades comprises the following components in parts by weight: 8-10 parts of reinforced composite filler and 520-660 parts of branched double bond self-healing polyurethane.
[0006] Preferably, the reinforced composite filler is prepared from the following components in parts by weight: 15-25 parts of mica, 6-8 parts of γ-methacryloxypropyltriethoxysilane, 3-4 parts of benzoylacetone, 2.5-3.5 parts of 3-bromopropylene and 5-6 parts of nano-alumina.
[0007] Preferably, the branched double-bond self-healing polyurethane is prepared from the following components in parts by weight: 40-50 parts of diphenylmethane diisocyanate, 8-12 parts of polytetrahydrofuran, 8-10 parts of polyethylene glycol, 1.2-2.3 parts of triphenylmethane triisocyanate, 5-6.5 parts of hydroxyethyl acrylate and 2-3 parts of 4,4'-dicarboxy diphenyl disulfide.
[0008] Preferably, the mica particle size is 15 um; the polytetrahydrofuran Mn=650; and the polyethylene glycol Mn=400.
[0009] Preferably, the preparation method of the reinforced composite filler specifically comprises the following steps:
[0010] (1) Adding nano-alumina in an amount of 0.2-0.3 g / mL to anhydrous ethanol, adding γ-methacryloxypropyltriethoxysilane, stirring in a water bath, and obtaining a modified alumina dispersion;
[0011] (2) dissolving benzoyl acetone in a 3-4 wt% sodium ethoxide ethanol solution at an addition amount of 0.16-0.22 g / mL, adding 3-bromopropylene dropwise, stirring in a water bath, and obtaining a reaction solution;
[0012] (3) The reaction solution obtained in step (2) is subjected to rotary evaporation to remove ethanol, and after cooling, 2 volumes of deionized water are added, the organic phase is separated and retained, washed 3-5 times, and dried over anhydrous magnesium sulfate to obtain a coordination modifier;
[0013] (4) Mica is added in anhydrous ethanol at an addition amount of 0.15-0.25 g / mL and uniformly dispersed, and the coordination modifier obtained in step (3) is added, followed by dropwise addition of 0.8-1.2% by mass of dibenzoyl peroxide and the modified alumina dispersion obtained in step (1), respectively, and stirred in a water bath, washed, and dried to obtain a reinforced composite filler.
[0014] Preferably, in step (1), the water bath is stirred at a temperature of 50-60° C., a speed of 800-1000 rpm, and a time of 20-30 min.
[0015] Preferably, in step (2), the water bath is stirred at a temperature of 60-70° C., a speed of 500-600 rpm, and a time of 60-80 min.
[0016] Preferably, in step (4), the water bath is stirred at a temperature of 70-80°C, a speed of 100-120 rpm, and a time of 30-50 min.
[0017] Preferably, the method for preparing the branched double-bond self-repairing polyurethane specifically comprises the following steps:
[0018] S1, adding triphenylmethane triisocyanate to acetone, then adding 1-1.5 wt ‰ of dibutyltin dilaurate, mixing evenly to obtain a mixed solution 1, adding hydroxyethyl acrylate to acetone, then adding 1.5-2 wt ‰ of 4-methoxyphenol, mixing evenly to obtain a mixed solution 2;
[0019] S2, heating the mixed solution 1 obtained in S1 to 60° C., adding the mixed solution 2 obtained in S1 dropwise into the mixed solution 1 obtained in S1, reacting in a water bath to obtain a reaction solution;
[0020] S3. Add diphenylmethane diisocyanate to the reaction solution obtained in S2, heat to 80°C under nitrogen protection, add polytetrahydrofuran, polyethylene glycol and 4,4'-dicarboxydiphenyl disulfide dropwise with stirring at 50-60rpm, and then stir in an oil bath to obtain a branched double-bond self-healing polyurethane.
[0021] Preferably, in S1, the amount of triphenylmethane triisocyanate added to acetone is 0.8-1 g / mL; the amount of hydroxyethyl acrylate added to acetone is 1.2-1.6 g / mL.
[0022] Preferably, in S2, the water bath reaction is carried out at a temperature of 60-70° C. for 4-5 h.
[0023] Preferably, in S3, the oil bath is stirred at a temperature of 80-90°C, a speed of 300-400 rpm, and a time of 30-50 min.
[0024] The present invention also provides a method for preparing a highly hydrophobic coating for fan blades, which specifically comprises the following steps:
[0025] The reinforced composite filler was added into the branched double-bond self-healing polyurethane, and 0.5wt‰ of dibenzoyl peroxide was added and mixed evenly to obtain a highly hydrophobic coating for the fan blades.
[0026] The beneficial effects achieved by the present invention are as follows: the present invention modifies nano alumina by γ-methacryloxypropyl triethoxysilane, and prepares mica modified by a complexing agent containing double bonds with benzoyl acetone and 3-propylene bromide, so that the mica is loaded with nano alumina, and the modification of organic matter enables it to be evenly dispersed in the polyurethane coating, and the double bonds with it can be polymerized with the polyurethane with double bonds in the subsequent step, thereby enhancing the cross-linking structure, strengthening the firm combination of the composite filler and the polyurethane, and enhancing the hydrophobicity, corrosion resistance and wear resistance; triphenylmethane triisocyanate is modified with hydroxyethyl acrylate to prepare a branched double bond and a bis-NCO prepolymer, polytetrahydrofuran and polyethylene glycol are used as soft segments, diphenylmethane diisocyanate is used as a hard segment, and 4,4'-dicarboxyl diphenyl disulfide is added, so that the prepared polyurethane has a branched double bond and self-healing ability. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The hydrophobic test results of Examples 1-3 and Comparative Examples 1-3 of the present invention are shown in FIG.
[0028] Figure 2 The wear test results of Examples 1-3 and Comparative Examples 1-3 of the present invention are shown in FIG.
[0029] Figure 3 The results of salt spray tests of Examples 1-3 and Comparative Examples 1-3 of the present invention are shown in FIG.
[0030] Figure 4 This is a self-repair test result diagram of Example 1 of the present invention and Comparative Example 4.
[0031] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention. DETAILED DESCRIPTION
[0032] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0033] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.
[0034] The experimental methods in the following examples are conventional methods unless otherwise specified; the experimental materials used in the following examples are purchased from commercial channels unless otherwise specified.
[0035] Example 1
[0036] A highly hydrophobic coating for wind turbine blades comprises the following components in parts by weight: 8 parts of a reinforced composite filler and 520 parts of a branched double-bond self-repairing polyurethane.
[0037] The reinforced composite filler is prepared from the following components in parts by weight: 15 parts of mica, 6 parts of gamma-methacryloxypropyltriethoxysilane, 3 parts of benzoylacetone, 2.5 parts of 3-bromopropylene and 5 parts of nano-alumina.
[0038] The branched double-bond self-healing polyurethane is prepared from the following components in parts by weight: 40 parts of diphenylmethane diisocyanate, 8 parts of polytetrahydrofuran, 8 parts of polyethylene glycol, 1.2 parts of triphenylmethane triisocyanate, 5 parts of hydroxyethyl acrylate and 2 parts of 4,4'-dicarboxy diphenyl disulfide.
[0039] The preparation method of the reinforced composite filler specifically comprises the following steps:
[0040] (1) Adding nano-alumina in anhydrous ethanol at an addition amount of 0.2 g / mL, adding γ-methacryloxypropyltriethoxysilane, and stirring at 800 rpm in a 50°C water bath for 20 min to obtain a modified alumina dispersion;
[0041] (2) dissolving benzoyl acetone in a 3 wt % sodium ethoxide ethanol solution at an addition amount of 0.16 g / mL, adding 3-bromopropylene dropwise, stirring at 500 rpm in a 60° C. water bath for 60 min, and obtaining a reaction solution;
[0042] (3) The reaction solution obtained in step (2) was subjected to rotary evaporation to remove ethanol, and after cooling, 2 volumes of deionized water were added, and the organic phase was retained after separation, and the organic phase was washed three times, and dried over anhydrous magnesium sulfate to obtain a coordination modifier;
[0043] (4) Mica is added in anhydrous ethanol at an addition amount of 0.15 g / mL and uniformly dispersed, and the coordination modifier obtained in step (3) is added, followed by dropwise addition of 0.8% by mass of dibenzoyl peroxide of mica and the modified alumina dispersion obtained in step (1), respectively. The mixture is stirred at 100 rpm in a 70°C water bath for 30 min, filtered, washed, and dried to obtain a reinforced composite filler.
[0044] The preparation method of the branched double-bond self-repairing polyurethane specifically comprises the following steps:
[0045] S1, adding triphenylmethane triisocyanate in an amount of 0.8 g / mL to acetone, then adding 1‰ of dibutyltin dilaurate, mixing evenly to obtain a mixed solution 1, adding hydroxyethyl acrylate in an amount of 1.2 g / mL to acetone, then adding 1.5wt‰ of 4-methoxyphenol, mixing evenly to obtain a mixed solution 2;
[0046] S2, heating the mixed solution 1 obtained in S1 to 60°C, adding the mixed solution 2 obtained in S1 dropwise to the mixed solution 1 obtained in S1, reacting in a water bath at 60°C for 4 hours to obtain a reaction solution;
[0047] S3. Add diphenylmethane diisocyanate to the reaction solution obtained in S2, heat to 80°C under nitrogen protection, add polytetrahydrofuran, polyethylene glycol and 4,4'-dicarboxydiphenyl disulfide dropwise with stirring at 50rpm, then stir at 80°C in an oil bath at 300rpm for 30min to obtain a branched double-bond self-healing polyurethane.
[0048] The present invention also provides a method for preparing a highly hydrophobic coating for fan blades, which specifically comprises the following steps:
[0049] The reinforced composite filler was added into the branched double-bond self-healing polyurethane, and 0.5wt‰ of dibenzoyl peroxide was added and mixed evenly to obtain a highly hydrophobic coating for the fan blades.
[0050] Example 2
[0051] A highly hydrophobic coating for wind turbine blades comprises the following components in parts by weight: 10 parts of reinforced composite filler and 660 parts of branched double-bond self-repairing polyurethane.
[0052] The reinforced composite filler is prepared from the following components in parts by weight: 25 parts of mica, 8 parts of gamma-methacryloxypropyltriethoxysilane, 4 parts of benzoylacetone, 3.5 parts of 3-bromopropylene and 6 parts of nano-alumina.
[0053] The branched double-bond self-healing polyurethane is prepared from the following components in parts by weight: 50 parts of diphenylmethane diisocyanate, 12 parts of polytetrahydrofuran, 10 parts of polyethylene glycol, 2.3 parts of triphenylmethane triisocyanate, 6.5 parts of hydroxyethyl acrylate and 3 parts of 4,4'-dicarboxy diphenyl disulfide.
[0054] The preparation method of the reinforced composite filler specifically comprises the following steps:
[0055] (1) Adding nano-alumina at an addition amount of 0.3 g / mL to anhydrous ethanol, adding γ-methacryloxypropyltriethoxysilane, stirring at 1000 rpm for 30 min in a 60°C water bath to obtain a modified alumina dispersion;
[0056] (2) dissolving benzoyl acetone in a 4 wt % sodium ethoxide ethanol solution at an addition amount of 0.22 g / mL, adding 3-bromopropylene dropwise, stirring at 5600 rpm in a 70° C. water bath for 80 min to obtain a reaction solution;
[0057] (3) The reaction solution obtained in step (2) was subjected to rotary evaporation to remove ethanol, and after cooling, 2 volumes of deionized water were added, and the organic phase was retained after separation, and the organic phase was washed 5 times, and dried over anhydrous magnesium sulfate to obtain a coordination modifier;
[0058] (4) Mica was added in anhydrous ethanol at an addition amount of 0.25 g / mL and uniformly dispersed, and the coordination modifier obtained in step (3) was added, followed by dropwise addition of 1.2% by mass of dibenzoyl peroxide of mica and the modified alumina dispersion obtained in step (1), respectively, and stirred at 120 rpm in a water bath at 80°C for 50 min, filtered, washed, and dried to obtain a reinforced composite filler.
[0059] The preparation method of the branched double-bond self-repairing polyurethane specifically comprises the following steps:
[0060] S1, adding triphenylmethane triisocyanate in an amount of 1 g / mL to acetone, then adding 1.5‰ of dibutyltin dilaurate, mixing evenly to obtain a mixed solution 1, adding hydroxyethyl acrylate in an amount of 1.6 g / mL to acetone, then adding 2wt‰ of 4-methoxyphenol, mixing evenly to obtain a mixed solution 2;
[0061] S2, heating the mixed solution 1 obtained in S1 to 60°C, adding the mixed solution 2 obtained in S1 dropwise to the mixed solution 1 obtained in S1, reacting in a water bath at 70°C for 5 hours to obtain a reaction solution;
[0062] S3. Add diphenylmethane diisocyanate to the reaction solution obtained in S2, heat to 80°C under nitrogen protection, add polytetrahydrofuran, polyethylene glycol and 4,4'-dicarboxydiphenyl disulfide dropwise with stirring at 60rpm, then stir at 90°C in an oil bath at 400rpm for 50min to obtain a branched double-bond self-healing polyurethane.
[0063] The present invention also provides a method for preparing a highly hydrophobic coating for fan blades, which specifically comprises the following steps:
[0064] The reinforced composite filler was added into the branched double-bond self-healing polyurethane, and 0.5wt‰ of dibenzoyl peroxide was added and mixed evenly to obtain a highly hydrophobic coating for the fan blades.
[0065] Example 3
[0066] A highly hydrophobic coating for wind turbine blades comprises the following components in parts by weight: 9 parts of reinforced composite filler and 600 parts of branched double-bond self-repairing polyurethane.
[0067] The reinforced composite filler is prepared from the following components in parts by weight: 20 parts of mica, 7 parts of gamma-methacryloxypropyltriethoxysilane, 3.5 parts of benzoylacetone, 3 parts of 3-bromopropylene and 5.5 parts of nano-alumina.
[0068] The branched double-bond self-healing polyurethane is prepared from the following components in parts by weight: 45 parts of diphenylmethane diisocyanate, 10 parts of polytetrahydrofuran, 9 parts of polyethylene glycol, 2 parts of triphenylmethane triisocyanate, 6 parts of hydroxyethyl acrylate and 2.5 parts of 4,4'-dicarboxy diphenyl disulfide.
[0069] The preparation method of the reinforced composite filler specifically comprises the following steps:
[0070] (1) Adding nano-alumina at an addition amount of 0.25 g / mL to anhydrous ethanol, adding γ-methacryloxypropyltriethoxysilane, stirring at 900 rpm in a 55°C water bath for 25 min to obtain a modified alumina dispersion;
[0071] (2) dissolving benzoylacetone in a 3.5 wt% sodium ethoxide ethanol solution at an addition amount of 0.2 g / mL, adding 3-bromopropylene dropwise, stirring at 550 rpm in a 65°C water bath for 70 min, and obtaining a reaction solution;
[0072] (3) The reaction solution obtained in step (2) was subjected to rotary evaporation to remove ethanol, and after cooling, 2 volumes of deionized water were added, and the organic phase was retained after separation, and the organic phase was washed 4 times, and dried over anhydrous magnesium sulfate to obtain a coordination modifier;
[0073] (4) Mica was added in anhydrous ethanol at an addition amount of 0.2 g / mL and uniformly dispersed, and the coordination modifier obtained in step (3) was added, followed by dropwise addition of 1% by mass of dibenzoyl peroxide of mica and the modified alumina dispersion obtained in step (1), respectively, and stirred at 110 rpm in a water bath at 75°C for 40 min, filtered, washed, and dried to obtain a reinforced composite filler.
[0074] The preparation method of the branched double-bond self-repairing polyurethane specifically comprises the following steps:
[0075] S1, adding triphenylmethane triisocyanate in an amount of 0.9 g / mL to acetone, then adding 1.3 wt ‰ of dibutyltin dilaurate, mixing evenly to obtain a mixed solution 1, adding hydroxyethyl acrylate in an amount of 1.4 g / mL to acetone, then adding 1.8 wt ‰ of 4-methoxyphenol, mixing evenly to obtain a mixed solution 2;
[0076] S2, heating the mixed solution 1 obtained in S1 to 60°C, adding the mixed solution 2 obtained in S1 dropwise to the mixed solution 1 obtained in S1, reacting in a water bath at 65°C for 4.5h to obtain a reaction solution;
[0077] S3. Add diphenylmethane diisocyanate to the reaction solution obtained in S2, heat to 80°C under nitrogen protection, add polytetrahydrofuran, polyethylene glycol and 4,4'-dicarboxydiphenyl disulfide dropwise with stirring at 55rpm, then stir at 85°C in an oil bath at 350rpm for 40min to obtain a branched double-bond self-healing polyurethane.
[0078] The present invention also provides a method for preparing a highly hydrophobic coating for fan blades, which specifically comprises the following steps:
[0079] The reinforced composite filler was added into the branched double-bond self-healing polyurethane, and 0.5wt‰ of dibenzoyl peroxide was added and mixed evenly to obtain a highly hydrophobic coating for the fan blades.
[0080] Comparative Example 1
[0081] This comparative example provides a coating, which differs from Example 1 only in that the components do not contain benzoylacetone and 3-bromopropylene, that is, no coordination modifier is prepared in step (3), and the remaining components and component contents are the same as those in Example 1.
[0082] Comparative Example 2
[0083] This comparative example provides a coating, which differs from Example 1 only in that the components do not contain γ-methacryloxypropyltriethoxysilane, and the remaining components and component contents are the same as those in Example 1.
[0084] Comparative Example 3
[0085] This comparative example provides a coating, which differs from Example 1 only in that triphenylmethane triisocyanate is not included in the components, and the remaining components and component contents are the same as those in Example 1.
[0086] Comparative Example 4
[0087] This comparative example provides a coating, which differs from Example 1 only in that the coating does not contain 4,4'-dicarboxy diphenyl disulfide, and the remaining components and component contents are the same as those in Example 1.
[0088] Experimental example
[0089] 1. Hydrophobicity test
[0090] Example 1-3 and comparative example 1-3 were sprayed on a steel plate with a coating thickness of 80 μm. After drying, 5 μl of water was respectively absorbed on the surface of each coating group. After 20 seconds, the material was placed on a test platform and the contact angle was measured using an SDC-350 contact angle meter.
[0091] Figure 1 It is a graph of the hydrophobic test results of Examples 1-3 of the present invention and Comparative Examples 1-3; as shown in the figure, the contact angles of Examples 1-3 and Comparative Examples 1-3 are 162.3°, 163.6°, 166.1°, 116.5°, 93.3°, and 136.8°, respectively. The contact angle of Example 1-3 is significantly greater than that of Comparative Example 1-3, indicating that the hydrophobicity of Example 1-3 is stronger than that of Comparative Example 1-3, and the preparation of the coordination modifier, the reinforced composite filler and the use of triphenylmethane triisocyanate improve the hydrophobicity of the material.
[0092] 2. Wear resistance test
[0093] Embodiment 1-3 and comparative example 1-3 were sprayed on steel plates with a coating thickness of 80 um. After drying, quartz sand with a diameter of 0.5-1 mm was dropped from a height of 30 cm with a flow rate of 3 m / s. The samples were impacted at an angle of 60°. Samples were taken every 5 seconds until the hydrophobicity of the samples was completely lost. The impact time of each group was recorded.
[0094] Figure 2 It is a graph of the wear resistance test results of Examples 1-3 of the present invention and Comparative Examples 1-3; as shown in the figure, the impact times of Examples 1-3 and Comparative Examples 1-3 are 180s, 180s, 180s, 120s, 100s, and 135s, respectively, and the impact time of Example 1-3 is significantly greater than that of Comparative Example 1-3, indicating that the wear resistance of Example 1-3 is stronger than that of Comparative Example 1-3, and the preparation of the coordination modifier, the reinforced composite filler and the use of triphenylmethane triisocyanate improve the wear resistance of the material.
[0095] 3. Salt spray test
[0096] Example 1-3 and Comparative Example 1-3 were sprayed on a steel plate with a coating thickness of 80 μm. After drying, a cutter was used to scratch through the coating until the steel plate was exposed and the edges were sealed with wax. The scratch was greater than 20 mm from any edge of the steel plate. The steel plate was placed in a 35°C salt spray box and the corrosion was recorded. When rust spots appeared on the plate surface or the rust at the scribe line spread more than 2 cm, it was recorded as the salt spray resistance time.
[0097] Figure 3 It is a salt spray test result diagram of Examples 1-3 of the present invention and Comparative Examples 1-3; as shown in the figure, the salt spray resistance time of Examples 1-3 and Comparative Examples 1-3 are 306.3h, 302.6h, 304.1h, 222.7h, 193.1h, and 249.5h, respectively, and the salt spray resistance time of Example 1-3 is significantly greater than that of Comparative Example 1-3, indicating that the corrosion resistance of Example 1-3 is stronger than that of Comparative Example 1-3, and the preparation of the coordination modifier, the reinforced composite filler and the use of triphenylmethane triisocyanate improve the corrosion resistance of the material.
[0098] 4. Self-healing test
[0099] Example 1 and Comparative Example 4 were sprayed on a steel plate with a coating thickness of 80 μm. After drying, according to the wear resistance test, quartz sand was used to impact for 30 seconds, and a hydrophobicity test was performed every 0.5 hours for a total of 4 times, and the contact angle was recorded;
[0100] Figure 4 It is a self-healing test result diagram of Example 1 and Comparative Example 4 of the present invention; as shown in the figure, after 4 tests, the contact angles of Example 1 are 142.3, 156.8, 159.8, and 161.4, respectively, and the contact angles of Comparative Example 4 are 97.2, 96.3, 96.6, and 96.8, respectively. The self-healing ability of Example 1 is significantly better than that of Comparative Example 4, and the use of 4,4'-dicarboxy diphenyl disulfide improves the self-healing ability of the material.
[0101] While the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that many changes, modifications, substitutions and variations can be made to the embodiments without departing from the principles and spirit of the invention.
[0102] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.
Claims
1. A highly hydrophobic coating for fan blades, characterized in that: The invention comprises the following components in parts by weight: 8-10 parts of a reinforced composite filler and 520-660 parts of a branched double-bond self-repairing polyurethane; the reinforced composite filler is prepared from the following components in parts by weight: 15-25 parts of mica, 6-8 parts of γ-methacryloxypropyltriethoxysilane, 3-4 parts of benzoylacetone, 2.5-3.5 parts of 3-bromopropylene and 5-6 parts of nano-alumina; the branched double-bond self-repairing polyurethane is prepared from the following components in parts by weight: 40-50 parts of diphenylmethane diisocyanate, 8-12 parts of polytetrahydrofuran, 8-10 parts of polyethylene glycol, 1.2-2.3 parts of triphenylmethane triisocyanate, 5-6.5 parts of hydroxyethyl acrylate and 2-3 parts of 4,4'-dicarboxyl diphenyl disulfide.
2. A method for preparing a highly hydrophobic coating for fan blades according to claim 1, characterized in that: The method specifically comprises the following steps: adding a reinforced composite filler into a branched double-bond self-repairing polyurethane, adding 0.5wt‰ of dibenzoyl peroxide, and mixing the mixture evenly to obtain a highly hydrophobic coating for fan blades.
3. The method for preparing a highly hydrophobic coating for fan blades according to claim 2, wherein: The preparation method of the reinforced composite filler specifically comprises the following steps: (1) Adding nano-alumina in an amount of 0.2-0.3 g / mL to anhydrous ethanol, adding γ-methacryloxypropyltriethoxysilane, stirring in a water bath, and obtaining a modified alumina dispersion; (2) dissolving benzoyl acetone in a 3-4 wt% sodium ethoxide ethanol solution at an addition amount of 0.16-0.22 g / mL, adding 3-bromopropylene dropwise, stirring in a water bath, and obtaining a reaction solution; (3) The reaction solution obtained in step (2) is subjected to rotary evaporation to remove ethanol, and after cooling, 2 volumes of deionized water are added, the organic phase is separated and retained, washed 3-5 times, and dried over anhydrous magnesium sulfate to obtain a coordination modifier; (4) Mica is added in anhydrous ethanol at an addition amount of 0.15-0.25 g / mL and uniformly dispersed, and the coordination modifier obtained in step (3) is added, followed by dropwise addition of 0.8-1.2% by mass of dibenzoyl peroxide and the modified alumina dispersion obtained in step (1), respectively, and stirred in a water bath, washed, and dried to obtain a reinforced composite filler.
4. The method for preparing a highly hydrophobic coating for fan blades according to claim 3, wherein: In step (1), the water bath is stirred at a temperature of 50-60°C, a speed of 800-1000 rpm, and a time of 20-30 min.
5. The method for preparing a highly hydrophobic coating for fan blades according to claim 4, wherein: In step (2), the water bath is stirred at a temperature of 60-70°C, a speed of 500-600 rpm, and a time of 60-80 min.
6. The method for preparing a highly hydrophobic coating for fan blades according to claim 5, characterized in that: In step (4), the water bath is stirred at a temperature of 70-80°C, a speed of 100-120 rpm, and a time of 30-50 min.
7. The method for preparing a highly hydrophobic coating for fan blades according to claim 3, characterized in that: The preparation method of the branched double-bond self-repairing polyurethane specifically comprises the following steps: S1, adding triphenylmethane triisocyanate to acetone, then adding 1-1.5 wt ‰ of dibutyltin dilaurate, mixing evenly to obtain a mixed solution 1, adding hydroxyethyl acrylate to acetone, then adding 1.5-2 wt ‰ of 4-methoxyphenol, mixing evenly to obtain a mixed solution 2; S2, heating the mixed solution 1 obtained in S1 to 60° C., adding the mixed solution 2 obtained in S1 dropwise into the mixed solution 1 obtained in S1, reacting in a water bath to obtain a reaction solution; S3. Add diphenylmethane diisocyanate to the reaction solution obtained in S2, heat to 80°C under nitrogen protection, add polytetrahydrofuran, polyethylene glycol and 4,4'-dicarboxydiphenyl disulfide dropwise with stirring at 50-60rpm, and then stir in an oil bath to obtain a branched double-bond self-healing polyurethane.
8. The method for preparing a highly hydrophobic coating for fan blades according to claim 7, characterized in that: In S1, the amount of triphenylmethane triisocyanate added to acetone is 0.8-1 g / mL; the amount of hydroxyethyl acrylate added to acetone is 1.2-1.6 g / mL.
9. The method for preparing a highly hydrophobic coating for fan blades according to claim 8, characterized in that: In S2, the water bath reaction is carried out at a temperature of 60-70° C. for 4-5 hours.
10. The method for preparing a highly hydrophobic coating for fan blades according to claim 9, characterized in that: In S3, the oil bath is stirred at a temperature of 80-90°C, a speed of 300-400 rpm, and a time of 30-50 min.
Citation Information
Patent Citations
Fabrication method of super-hydrophobic / super-hydrophilic electrolyte lithium battery separator
CN109768205A
Wear-resistant corrosion-resistant super-hydrophobic composite coating and preparation method thereof
CN113698850A
Super-hydrophobic self-repairing transparent coating as well as preparation method and application thereof
CN116640511A
Photocuring self-repairing fluorine-silicon super-hydrophobic coating as well as preparation method and application thereof
CN116970337A
Hydrogen permeation resistant composite resin coating as well as preparation method and application thereof
CN118995007A